Suicide and self-harm content on Instagram: A systematic scoping review. - Jacobo Picardo; Sarah K McKenzie; Sunny Collings; Gabrielle Jenkin (PLoS ONE)
Given concerns about suicide or self-harm content on Instagram, we conducted a systematic scoping review of peer-reviewed English language primary studies published between 2010-2019. Only ten studies had been published. Looking into purposive samples of Instagram posts tagged with self-harm related hashtags, studies report finding self-harm or suicide content in between 9-66% of their studied posts. Studies assessing Instagram's efforts to tackle such content found they had not been very effective. Despite heterogeneity in study aims, use of terminology, samples, methods of analysis, and study outcomes, we aggregated and distinguished 'content studies' and 'user studies'. Most studies showed concern for self-harm risk, but only one examined the relationship between self-harm posts and actual self-harm behaviours offline. It found such content had negative emotional effects on some users and reported preliminary evidence of potential harmful effects in relation to self-harm related behaviours offline, although causal effects cannot be claimed. At the same time, some benefits for those who engage with self-harm content online have been suggested. More research directly interviewing Instagram users to understand this phenomenon from their perspective is required. Finally, some ethical issues are discussed.